Effect of gemfibrozil and rifampicin on the pharmacokinetics of selexipag and its active metabolite in healthy subjects - Bruderer, Shirin (Br J Clin Pharmacol, 2017)
AIMS: Based on in vitro data, there is evidence to suggest that cytochrome P450 (CYP) 2C8 is involved in the metabolism of selexipag and its active metabolite, ACT‐333679. The present study evaluated the possible pharmacokinetic interactions of selexipag with gemfibrozil, a strong CYP2C8 inhibitor, and rifampicin, an inducer of CYP2C8. METHODS: The study consisted of two independent parts, each conducted according to an open‐label, randomized, crossover design. The pharmacokinetics and safety of selexipag and ACT‐333679 were studied following single‐dose administration either alone or in the presence of multiple‐dose gemfibrozil (part I) or rifampicin (part II) in healthy male subjects. RESULTS: Gemfibrozil had comparatively small effects on selexipag (less than 2‐fold difference in any pharmacokinetic variable) but, with respect to ACT‐333679, increased the maximum plasma concentration (C(max)) 3.6‐fold [90% confidence interval (CI) 3.1, 4.3] and the area under the plasma concentration–time curve from zero to infinity (AUC(0–∞)) 11.1‐fold (90% CI 9.2, 13.4). The marked increased exposure to ACT‐333679, which mediates the majority of the pharmacological activity of selexipag, was accompanied by significantly more adverse events such as headache, nausea and vomiting. Coadministration of rifampicin increased the C(max) of selexipag 1.8‐fold (90% CI 1.4, 2.2) and its AUC0(–∞) 1.3‐fold (90% CI 1.1, 1.4); its effects on ACT‐333679 were to increase its C(max) 1.3‐fold (90% CI 1.1, 1.6), shorten its half‐life by 63% and reduce its AUC0(–∞) by half (90% CI 0.45, 0.59). CONCLUSION: Concomitant administration of selexipag and strong inhibitors of CYP2C8 must be avoided, whereas when coadministered with inducers of CYP2C8, dose adjustments of selexipag should be envisaged.